The impact of renin-angiotensin-aldosterone system inhibitors on Type 1 and Type 2 diabetic patients with and without early diabetic nephropathy - Taylor, K; Stevens, R; Blacklock, C; Roberts, N; Pugh, C; Farmer, A; Hirst, J (2012)
Renin-angiotensin-aldosterone system inhibitors prevent the progression of kidney disease in patients with diabetic nephropathy, and we studied how that benefit varies by the type of diabetes and baseline urinary albumin. We pooled data from 49 randomized controlled trials in a meta-analysis using the ratio of endpoint urinary albumin levels in those treated compared to those untreated with renin-angiotensin-aldosterone system inhibitors in both fixed- and random-effects models. The urinary albumin excretion for treated microalbuminuric patients with Type 1 diabetes was on average 60% lower at the end of the trial compared with patients not treated with renin-angiotensin- aldosterone system inhibitors using the fixed-effects model and 67% lower using the random-effects model. There was no significant effect of treatment in patients with normal albumin excretion. For normoalbuminuric patients with Type 2 diabetes, urinary albumin excretion was on average 12% lower after treatment using the fixed-effects model compared to 21% lower using the random-effects model. For microalbuminuric patients, urinary albumin excretion was on average 23% lower using the fixed-effects model and 27% lower using the random-effects model. Thus, renin-angiotensin-aldosterone system inhibition reduced urinary albumin excretion for Type 1 diabetic patients with micro-, but not those with normoalbuminuria. Treatment reduced urinary albumin excretion for Type 2 diabetic patients with and without microalbuminuria. © 2012 International Society of Nephrology.